2013
DOI: 10.1007/s11207-013-0424-3
|View full text |Cite
|
Sign up to set email alerts
|

Migration and Extension of Solar Active Longitudinal Zones

Abstract: Solar active longitudes show a characteristic migration pattern in the Carrington coordinate system when they can be identified at all. By following this migration, the longitudinal activity distribution around the center of the band can be determined. The halfwidth of the distribution is found to be varying in Cycles 21 - 23, and in some time intervals it was as narrow as 20 - 30 degrees. It was more extended around maximum but it was also narrow when the activity jumped to the opposite longitude. Flux emerge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 29 publications
(46 reference statements)
2
15
0
Order By: Relevance
“…The shape of migration clearly follows parabolicshaped path as found in several earlier studies ( 2011a; Usoskin et al 2007Usoskin et al , 2005Gyenge et al 2014).…”
Section: Solar Non-axisymmetric Activitysupporting
confidence: 84%
See 1 more Smart Citation
“…The shape of migration clearly follows parabolicshaped path as found in several earlier studies ( 2011a; Usoskin et al 2007Usoskin et al , 2005Gyenge et al 2014).…”
Section: Solar Non-axisymmetric Activitysupporting
confidence: 84%
“…The role of differential rotation is also controversy. Various studies concluded that the differential rotation is not the reason of the migration of the AL (Balthasar 2007;Juckett 2006Juckett , 2007Gyenge et al 2014).…”
Section: Solar Non-axisymmetric Activitymentioning
confidence: 99%
“…Follow-up studies concerning the preferred locations (longitudes) of sunspot formation delivered inconsistent and partly contradictory results. Even today, the possible number, migration, life times, longterm behavior and the particular method to track them remain a subject of debate (see Berdyugina and Usoskin 2003;Usoskin et al 2005;Pelt et al 2006;Usoskin et al 2007;Weber et al 2013;Gyenge et al 2014). …”
Section: Cyclic Changes Of the Coronal Magnetic Fieldmentioning
confidence: 99%
“…The long homogeneous series of sunspot data is indispensable for studies of long-term processes. This has been exploited by Gyenge, Baranyi, and Ludmány (2014) in tracking the migration of solar active longitudes. After comparing the positions of flares and active longitudes, Gyenge, Ludmány, and Baranyi (2016) showed that the most flare-productive active regions tend to be located in or close to the active longitudinal belt.…”
Section: Examples For the Exploitation Of The Databasesmentioning
confidence: 99%